The Political economy of the Philippine-Taiwan relations the issue of migrant labor - Lopega, Diosdado B. (2016)
This study looks into the political economy of the relations between the Philippines and Taiwan taking into account the issue of migrant labor as a factor in the conduct of their relations. This is a qualitative study and it utilizes the theory of trans-governmentalism in understanding the mechanics of their relationship. This paper contends that despite the absence of diplomatic ties, this relationship is made vibrant because of the issue of migrant labor as a talking point and the role of civil-society groups in the process. However, the quality of the migrant labor policies implemented by both governments is affected by political and economic factors from both sides. It is therefore not unusual that in the conduct of their relations the Overseas Filipino Workers (OFWs) are used as a fluid tool by Taiwan to get the Philippines kowtow to its demands. Taiwan feels that since the Philippines desperately needs to improve its economy by relying on remittances of the OFWs, Taiwan can always draw the issue of migrant labor against the Philippines. But the Philippines, together with civil society organizations knows that since Taiwan desperately needs a diplomatic breathing space in the international community, the Philippines can request Taiwan to treat the OFWs along international labor standards, lest it be accused of violating international labor norms in its own yard. Taiwan cannot afford to be labeled as an international pariah therefore it has to tow the line. So far the relationship of the two countries is mutually beneficial, with the issue of migrant labor serving as an important link in their relations.
Keywords: Migrant labor (Foreign workers)